Did prioritizing essential workers help to achieve racial/ethnic equity in early COVID‐19 vaccine distribution? The LA pandemic surveillance cohort study. Issue 4 (20th February 2022) - Nicholas, Will; Sood, Neeraj; Lam, Chun Nok; Kotha, Rani; Hu, Howard; Simon, Paul
Abstract: Background: Most US states and counties prioritized essential workers for early access to COVID‐19 vaccines due to their heightened occupational risk. Racial/ethnic groups most impacted by COVID‐19 are overrepresented among essential workers. This study estimates the effects of prioritizing essential workers on racial/ethnic equity in COVID‐19 vaccination. Methods: Survey data were collected from 5500 Los Angeles County adult residents in March and April 2021. Multivariate regression models were used to assess marginal changes in probabilities of vaccination attributable to essential worker status by race/ethnicity. These probabilities were multiplied by population proportions of essential workers in each racial/ethnic group to estimate the effects of prioritizing essential workers on vaccine equity in the population. Results: While Latinos (24.9%), Blacks (22.4%), and Asians (21.4%) were more likely to be prioritized essential workers than Whites (14.3%), their marginal gains in vaccine uptake due to their essential worker status did not significantly differ from that of Whites. At the population‐level, prioritizing vaccines for essential workers increased the probabilities of vaccination by small and similar amounts among Asians (5.3%; 95% confidence interval [CI]: 3.3%, 7.5%), Blacks (4.0%; 95% CI: 1.7%, 6.5%), Latinos (3.7%; 95% CI: 2.3%, 5.1%), and Whites (2.9%; 95% CI :1.9%, 3.9%). Conclusions: Prioritizing essential workers did not provide proportionally greater early vaccine uptake benefits to racial/ethnic groups that were disproportionately affected by COVID‐19. Early prioritization of essential workers during vaccine campaigns is an important but insufficient strategy for reducing racial/ethnic disparities in early vaccine uptake. Additional strategies addressing access and trust are needed to achieve greater equity in vaccine distribution.